Islamic Education Teachers Efforts in Instilling Ahlussunah Waljamaah an-Nahdliyah Values of Nahdlatul Ulama Vocational Students, Lamongan - Moch Faizin Muflich; Aridlah Sendy Robikhah; Lusia Mumtahana; Anni Fatimatus Sholikhah (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2023)
This study explains the instilling of the values of Ahlussunnah Wal Jamaah An-Nahdliyyah in SMK NU students Lamongan by Islamic education teachers to overcome students who are in a moral and ethical crisis so that their behavior deviates from the teachings of values which lead to disagreements between one another and can lead to intolerance and extremes. The research method used is qualitative, then data collection uses observation, interviews, and documentation, then data analysis includes data collection, data condensation, data display, and data verification. This study indicates that the efforts made by Islamic Education Teachers in instilling the values of Ahlussunnah Wal Jamaah An-Nahdliyyah go through three stages. First, the value transformation stage, through the provision of understanding, and advice. Second, the value transaction stage, through religious activities, instills morals. Third, the stages of trans-internalization of values, through habituation of amaliyah, exemplary and balance in the world and the hereafter. Supporting factors are a majority of Nahdlatul Ulama members, teacher professionalism, and effective Ahlussunnah Wal Jamaah learning. The inhibiting factors are lack of literature, students being less responsive, and less discipline. Efforts to prevent the presence of inhibiting factors include adding literature reviews, increasing the creativity of educators, and the need for a personal approach.